Evaluation of the antioxidant activities and nutritional properties of ten edible plant extracts and their application to fresh ground beef - Kim, Sung-Jin; Min, Sea C.; Shin, Hyo-Jin; Lee, Yun-Jeong; Cho, Ah Reum; Kim, So Yeon; Han, Jaejoon (ELSEVIER SCI LTD, 2013)
In this study, we assessed the antioxidant efficacy and nutritional value of 10 leafy edible plants and evaluated their potential as natural antioxidants for meat preservation. We measured total phenolic content, 2,2-diphenyl-1-picryl-hydrazil (DPPH) radical scavenging activity, and vitamin C, chlorophyll, and carotenoid contents of 70% ethanol and water extracts of the edible plants. Based on these results, we investigated the effects of butterbur and broccoli extracts on lipid oxidation in ground beef patties. Plant extracts and butylated hydroxytoluene (BHT) were individually added to patties at both 0.1% and 0.5% (w/w) concentrations. Thiobarbituric acid reactive substance (TBARS) values and color parameters were tested periodically during 12 days of refrigerated storage. TBARS levels were significantly lower (p <= 0.05) in the samples containing plant extracts or BHT than the non-treated control. In addition, the beef patties formulated with the selected plant extracts showed significantly (p <= 0.05) better color stability than those without antioxidants. These results indicate that edible plant extracts are promising sources of natural antioxidants and can potentially be used as functional preservatives in meat products. (c) 2012 Elsevier Ltd. All rights reserved.